Perceptions of Anatomy Education among Radiological Techniques Students in Iraq: A Cross-Sectional Study - Madhi, Zaid Saad; Hasan , Mohannad Ali; Al-Algawy, Alaa A.Hussein; Abed Madhi , Saad (Hammurabi Journal of Medical Sciences, 2026)
Background: Anatomy is a cornerstone in medical education for all medical and healthcare specialties. It provides students with the foundational knowledge needed to build concepts for understanding clinical scenarios, identifying anatomical abnormalities, and delivering safe clinical practice. Objectives: The objectives of this study are to identify factors influencing student satisfaction with anatomy education and their association with academic performance among radiological techniques students in Iraq. Materials and Methods: This is a cross-sectional study of 421 radiological techniques students across all academic years conducted in Babylon, Iraq. A locally developed, validated questionnaire was used to assess perceptions of anatomy education. Results: Student satisfaction was significantly associated with lecture quality (χ² = 166.69, p < 0.001), lecturer performance (χ² = 168.12, p < 0.001), practical laboratory experience (χ² = 65.90, p < 0.001), technology integration (χ² = 37.10, p < 0.001), and clinical relevance (χ² = 158.37, p < 0.001). Similarly, examination performance was significantly associated with lecturer performance (χ² = 58.77, p < 0.001), lecture quality (χ² = 80.53, p < 0.001), practical labs (χ² = 65.90, p < 0.001), technology integration (χ² = 37.10, p < 0.001), and clinical relevance (χ² = 18.67, p < 0.001). Conclusion: Student satisfaction with anatomy education among radiological techniques students in Iraq is most determined by the performance of the lecturers and the quality of their lectures, followed by the availability of hands-on practical laboratory experiences. These factors are essential in developing confident clinical staff and promoting healthcare